2023
DOI: 10.1186/s12876-023-02788-2
|View full text |Cite
|
Sign up to set email alerts
|

A single-center prospective study evaluating the usefulness of artificial intelligence for the diagnosis of esophageal squamous cell carcinoma in a real-time setting

Abstract: Background Several pre-clinical studies have reported the usefulness of artificial intelligence (AI) systems in the diagnosis of esophageal squamous cell carcinoma (ESCC). We conducted this study to evaluate the usefulness of an AI system for real-time diagnosis of ESCC in a clinical setting. Methods This study followed a single-center prospective single-arm non-inferiority design. Patients at high risk for ESCC were recruited and real-time diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Finally, 19 papers relating to AI‐assisted diagnosis of early EC and its invasion depth were included in the study. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 By analyzing endoscopic WLI/NBI, the sensitivity and specificity of AI‐assisted systems, novices, and experts in the diagnosis of early EC and its infiltration depth were compared in these studies, respectively. The literature search process is shown in Figure 1 , and the basic information of each study was extracted (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 19 papers relating to AI‐assisted diagnosis of early EC and its invasion depth were included in the study. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 By analyzing endoscopic WLI/NBI, the sensitivity and specificity of AI‐assisted systems, novices, and experts in the diagnosis of early EC and its infiltration depth were compared in these studies, respectively. The literature search process is shown in Figure 1 , and the basic information of each study was extracted (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This enables the AI system to identify ECs of different types and degrees of condition, including early lesions, thus improving the comprehensiveness of diagnosis. 17 In addition, the AI system has a unique advantage in image analysis, which allows it to quickly and accurately analyze a large number of endoscopic images and effectively detect tiny lesions or abnormalities, thus helping in the timely detection of early EC. Yang et al 21 found that the AI system, trained through simulation, diagnosed early EC with an accuracy of 88.1% in the evaluation of 1097 WLI, which was higher than that of experienced endoscopists (84.5%) and low‐ranking physicians (68.5%), and there was an obvious increase in sensitivity (90.1% vs. 86.4% vs. 72.7%) and specificity (85% vs. 82.5% vs. 63.7%), showing that the AI system can reach the level of endoscopists after training.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy, sensitivity and specificity of the AI systems were 80.6%, 68.2%, and 83.4%, respectively. In contrast, endoscopic physicians exhibited increased accuracy (85.7%) but decreased sensitivity (61.4%) and specificity (91.2%)[ 115 ]. Although there are still several limitations in the early detection of ESCC using AI, such as issues related to data quality, unreliable results, and the need for verification by professional doctors, significant improvements can be achieved by establishing comprehensive databases, enhancing model interpretability, integrating multimodal information, and strengthening self-learning capabilities.…”
Section: Endoscopy and Aimentioning
confidence: 99%